Development of Sensor Training Kit for STEM Education Application (Primary and Secondary School) - Suaimi, Muhammad Umar Yazid; Sadun, Amirul Syafiq (Progress in Engineering Application and Technology, 2023)
Recently there has been an increase in providing students with an initial knowledge of the rapidly evolving field of robotics especially in the field of STEM education in primary and secondary. The application of sensors without a good fundamental understanding of the operating structure will definitely make it difficult for students to understand more complex robotic systems. Therefore, a STEM training kit that needs to be developed to teach them the basics of different types of sensors is important, especially the use of STEM education. This STEM Sensor Kit will have multiple types of sensors. This project utilizes LabVIEW GUI to train the students basic functioning of various sensors incorporating Arduino UNO as data acquisition device. Through the analysis, it was concluded that the sensor training system was highly effective in teaching students the fundamentals of sensor technology in a way that was easy to understand.